The developing regime of the high seas in the context of exercise of jurisdiction over foreign ships - Economides, John (Department of Commercial Law, 2021)
This dissertation deals with the public international law aspect of the developing regime of the high seas in the context of jurisdiction over foreign ships and it confines itself primarily to the jurisdictional issues.